Anandamide Capacitates Bull Spermatozoa through CB1 and TRPV1 Activation - Gervasi, María Gracia; Osycka-Salut, Claudia; Caballero, Julieta; Vazquez-Levin, Mónica; Pereyra, Elba; Billi, Silvia; Franchi, Ana; Perez-Martinez, Silvina (PLOS ONE, 2011)
Anandamide (AEA), a major endocannabinoid, binds to cannabinoid and vanilloid receptors (CB1, CB2 and TRPV1) and affects many reproductive functions. Nanomolar levels of anandamide are found in reproductive fluids including mid-cycle oviductal fluid. Previously, we found that R(+)-methanandamide, an anandamide analogue, induces sperm releasing from bovine oviductal epithelium and the CB1 antagonist, SR141716A, reversed this effect. Since sperm detachment may be due to surface remodeling brought about by capacitation, the aim of this paper was to investigate whether anandamide at physiological concentrations could act as a capacitating agent in bull spermatozoa. We demonstrated that at nanomolar concentrations R(+)-methanandamide or anandamide induced bull sperm capacitation, whereas SR141716A and capsazepine (a TRPV1 antagonist) inhibited this induction. Previous studies indicate that mammalian spermatozoa possess the enzymatic machinery to produce and degrade their own AEA via the actions of the AEA-synthesizing phospholipase D and the fatty acid amide hydrolase (FAAH) respectively. Our results indicated that, URB597, a potent inhibitor of the FAAH, produced effects on bovine sperm capacitation similar to those elicited by exogenous AEA suggesting that this process is normally regulated by an endogenous tone. We also investigated whether anandamide is involved in bovine heparin-capacitated spermatozoa, since heparin is a known capacitating agent of bovine sperm. When the spermatozoa were incubated in the presence of R(+)-methanandamide and heparin, the percentage of capacitated spermatozoa was similar to that in the presence of R(+)-methanandamide alone. The pre-incubation with CB1 or TRPV1 antagonists inhibited heparin-induced sperm capacitation; moreover the activity of FAAH was 30% lower in heparin-capacitated spermatozoa as compared to control conditions. This suggests that heparin may increase endogenous anandamide levels. Our findings indicate that anandamide induces sperm capacitation through the activation of CB1 and TRPV1 receptors and could be involved in the same molecular pathway as heparin in bovines.